The Sideways March: Mackenzie King’s Monumental Quest, 1893-1940 - Duffy, Dennis (Ontario History)

(untitled) (The Ontario Historical Society, 2008)
This article concludes with William Lyon Mackenzie King’s successful diversion of the public memory of the struggle for responsible government from its various historical proponents to his grandfather, William Lyon Mackenzie. This he accomplished through his influence on monuments erected in Ontario during his heyday. The article follows this progress as it ambles through a number of other monuments and popular texts, culminating in an idealized testament to an individual apotheosized into a near-allegorical political presence.